2010
DOI: 10.1017/s0960258510000358
|View full text |Cite
|
Sign up to set email alerts
|

Seed mass and shape are related to persistence in a sandy soil in northern China

Abstract: Whether and how seed mass and shape are related to seed persistence in soil is a controversial topic in plant ecology. There is little information on this relationship in sandy habitats. We tested whether or not this pattern is retained among 141 species within a range of growth forms, from a wide range of families, in the Horqin sandy land of northern China, which belongs to the inland sand ecosystem. We collected information on seed mass, shape and persistence of these species in this region from published a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…We found that predicted persistence times were unrelated to any of the morphological traits of the control seeds available, which contradicts the previously published literature data (e.g. [6,7,19,45,47]). Nevertheless, we found that a relative change in seed mass affected the predicted persistence.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that predicted persistence times were unrelated to any of the morphological traits of the control seeds available, which contradicts the previously published literature data (e.g. [6,7,19,45,47]). Nevertheless, we found that a relative change in seed mass affected the predicted persistence.…”
Section: Discussioncontrasting
confidence: 99%
“…Bekker et al (1998a) found that larger seeds and seeds with large surface area to volume ratios tend to be shorter-lived and are not incorporated into the soil as easily as their smaller, rounder counterparts, which fall easily through cracks and are more readily transported by earthworms. A positive relationship between small seed size and longer persistence was also demonstrated in the flora of Britain (Hodkinson et al, 1998), Argentina (Funes et al, 1999), Iran (Thompson et al, 2001) and northern China (Zhao et al, 2011b). Moreover, small rounded seeds may be more resistant to fire, and thereby more persistent in environments where fire frequency is high (Gómez-González et al, 2011).…”
Section: (A) Seed Size and Embryo-endosperm Proportionsmentioning
confidence: 88%
“…Mobile dunes, semi-stabilized dunes, and stabilized dunes are distributed over some areas of the steppe. In degraded sandy grasslands, seedlings are vulnerable to desiccation, long periods of drought, high temperatures, and overgrazing (Liu et al, 2007 ; Zhao et al, 2011 ). Seed germination strategies are, in theory, some of the most effective strategies for plants inhabiting arid environments, which are typically characterized by highly variable and unpredictable environment (Philippi, 1993 ).…”
Section: Introductionmentioning
confidence: 99%